Language learning strategies - Jalo, Marcela Lilian (2005)
If a principle guiding the goals and purposes of the school of the 21st Century were to be chosen, undoubtedly the more accepted one among educators and researchers would be that education has to be directed to help students to learn how to learn. One of the functions of future education should be to promote the capacity of students to manage their own learning, to adopt a growing autonomy and to have intellectual and social tools that allow them continuous learning throughout their lives. In an increasingly open and complex society, there is a growing insistence on the fact that education should be directed to promote capacities and competences, not only closed knowledge or programmed techniques.